(3CcaGQ GdeJChdjfs - (3eMeO Hf GdWjH Hf eMeO Hf LYaQ, Jbj GdOjf CHh HcQ, GdbGVj GdHGbdGfj , J (B403 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg Hbhdg (B: (3bjd dge heG ai LeYg Hjf KdGKI eYGUi cd TF efgG djS HcaQ Ydi LOJg s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3aEf bGd bGFd (B: (3de de JZdhG Mce GdTgGOJjf Ydi Mce gPg GdePGgH EPG cGf CgdgG jbQhf HgeG s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds